W poszukiwaniu nowych źródeł przewagi konkurencyjnej: uwaga przedsiębiorcza i przedsiębiorczość organizacyjna - Zbierowski, Przemysław (Searching for sources of competitive advantage: entrepreneurial attention and organizational entrepreneurship, 2005)
The paper presents the conceptualization and operationalization of entrepreneurial attention, which is the adaptation of attention-based view of the firm and organizational attention to the theory and research in entrepreneurship. The findings of empirical research suggest the existence of dimensions of entrepreneurial attention, and their influence on organizational entrepreneurship. Moreover the potential of influence of entrepreneurial attention on organizational entrepreneurship has been measured, also the practical implications of research for managers are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 463-471